“Tupi, or not Tupi that is the question”: Amerindian perspectivism and Organizational Studies - Sergio Eduardo de Pinho Velho Wanderley; Ana Paula Medeiros Bauer (RAE: Revista de Administração de Empresas, 2020)
This essay discusses the possibilities that Viveiros de Castro's concept of Amerindian perspectivism offers to Organizational Studies. Oswald de Andrdade's Anthropophagous Manifesto is the guiding thread of our investigation. Amerindian perspectivism suggests a reflexive shift to the position occupied by the object of inquiry which thus becomes the subject from which we must question our own premises. What matters is knowing how our subject / former object perceives our categories / concepts created to describe it. For Viveiros de Castro, the reflexive displacement should occur considering an intentional equivocity. Therefore, we must reflect on the consequences that our onto-epistemological choices will have on our research from the Other's point of view. The concepts of reflexive displacement and intentional equivocity have much to contribute to the construction of the other in EOR and to the concept of border thinking in decolonial studies.